INVERSION OF HIGH FREQUENCY SURFACE WAVES WITH FUNDAMENTAL AND HIGHER MODES - Xia J.; Miller R.D.; Park C.B.; Tian G. (My University, 2003)
The phase velocity of Rayleigh-waves of a layered earth model is a function of frequency and four groups of earth parameters: compressional (P)-wave velocity, shear (S)-wave velocity, density, and thickness of layers. For the fundamental mode of Rayleigh waves, analysis of the Jacobian matrix for high frequencies (2-40 Hz) provides a measure of dispersion curve sensitivity to earth model parameters. S-wave velocities are the dominant influence of the four earth model parameters. This thesis is true for higher modes of high frequency Rayleigh waves as well. Our numerical modeling by analysis of the Jacobian matrix supports at least two quite exciting higher mode properties. First, for fundamental and higher mode Rayleigh wave data with the same wavelength, higher modes can ''see'' deeper than the fundamental mode. Second, higher mode data can increase the resolution of the inverted S-wave velocities. Real world examples show that the inversion process can be stabilized and resolution of the S-wave velocity model can be improved when simultaneously inverting the fundamental and higher mode data.
Keywords: SURFACE WAVES; HIGHER MODES; SHEAR WAVE VELOCITY; RESOLUTION; INVERSION